Efficacy and safety of esketamine in patients undergoing painless gastrointestinal endoscopy: a systematic review and meta-analysis of randomized controlled trials - Zhang, Qi; Wang, Qinghui (Frontiers in Medicine, 2025)
BackgroundEsketamine, an intravenous anesthetic with analgesic properties, is increasingly used as an adjunct in painless gastrointestinal endoscopy. This systematic review and meta-analysis evaluated the efficacy and safety of esketamine combined with sedatives for anesthesia in adults undergoing painless gastrointestinal endoscopy.MethodsEight databases (PubMed, Web of Science, EMBASE, Cochrane Library, CNKI, Wanfang, VIP, SinoMed) were systematically searched from inception until April 20, 2025. Randomized controlled trials (RCTs) comparing esketamine adjunctive therapy against placebo/sedative-alone in adults (ASA I-II) were included. Primary efficacy outcomes were anesthesia onset time, recovery time, and sedative requirements. Primary safety outcomes included procedure-related adverse events, and postoperative complications. Data synthesis was performed by using Review Manager 5.4 software. Subgroup analyses examined sedative type and esketamine dose.ResultsFifteen RCTs (n = 2,260 patients) were included. Esketamine adjunctive therapy significantly reduced anesthesia onset time (MD: −6.41 s, 95% CI: −10.42 to −2.40; p = 0.002) and total sedative requirements (SMD: −1.56, 95% CI: −1.92 to −1.20; p < 0.00001), corresponding to approximately 25–30% dose reduction. Sensitivity analysis excluding supratherapeutic doses (≥0.4 mg/kg) revealed significantly shorter recovery time (MD: −0.74 min, 95% CI: −1.17 to −0.31; p = 0.0008). Subgroup analysis identified the optimal dose window as 0.2–0.3 mg/kg, demonstrating maximal efficacy for onset time (MD: −9.75 min), recovery time (MD: −1.02 min), and sedative sparing. Safety outcomes indicated significantly reduced intraoperative hypotension, bradycardia, apnea, cough, body movement and injection pain, alongside transient increases in HR and MAP during instrumentation without clinically significant SpO2 changes. Significantly increased postoperative dizziness occurred, particularly at doses ≥0.3 mg/kg, with no significant association to postoperative nausea/vomiting or drowsiness.ConclusionEsketamine adjunctive therapy (optimal dose: 0.2–0.3 mg/kg) enhances sedation efficacy for painless gastrointestinal endoscopy by accelerating anesthesia onset, reducing sedative requirements, shortening recovery time, and decreasing intraoperative cardiorespiratory adverse events. Its primary safety concern is dose-dependent postoperative dizziness. Further large-scale, multinational trials are warranted to validate generalizability.Systematic review registrationCRD420251024070; https://www.crd.york.ac.uk/PROSPERO/view/CRD420251024070.